Những câu hỏi liên quan
H24
Xem chi tiết
TP
20 tháng 8 2016 lúc 15:06

B=3003x30013001-3001x30033003 

=> B = 0 

Bình luận (0)
AM
20 tháng 8 2016 lúc 15:07

\(B=3003.30013001-3001.30033003\)

\(B=3003.3001.10001-3001.3003.10001\)

\(B=0\)

Bình luận (0)
LA
20 tháng 8 2016 lúc 15:08

\(B=3003\times30013001-3001\times30033003=3003\times3001\times10001-3001\times3003\times10001\)

\(=3003\times3001\times10001\times\left(1-1\right)=3003\times3001\times10001\times0=0\)

Bình luận (0)
ML
Xem chi tiết
NT
17 tháng 3 2023 lúc 18:10

loading...  

Bình luận (0)
NB
Xem chi tiết
H24

-180

Bình luận (0)
NL
6 tháng 12 2021 lúc 18:13

-180

Bình luận (0)
NB
6 tháng 12 2021 lúc 18:16

tính đoàng hoàng đi

 

Bình luận (0)
H24
Xem chi tiết
H24
27 tháng 12 2021 lúc 15:34

Đặt tính rồi tính: 91,08 : 3,6 | VietJack.com

Bình luận (0)
TQ
27 tháng 12 2021 lúc 15:35

25,3

Bình luận (0)
TQ
27 tháng 12 2021 lúc 15:38

undefined

Bình luận (0)
NN
Xem chi tiết
H24
Xem chi tiết
H24
Xem chi tiết
NT
13 tháng 7 2023 lúc 11:33

Sửa đề: 3/91*96

\(B=\dfrac{3}{1\cdot6}+\dfrac{3}{6\cdot11}+...+\dfrac{3}{91\cdot96}\)

=3/5(5/1*6+5/6*11+...+5/91*96)

=3/5(1-1/6+1/6-1/11+...+1/91-1/96)

=3/5*95/96=57/96=19/32

Bình luận (0)
TK
Xem chi tiết
NT
10 tháng 1 2022 lúc 17:05

Bài 1: 

b: \(=\left(\dfrac{27}{23}-\dfrac{4}{23}\right)+\left(\dfrac{5}{21}+\dfrac{16}{21}\right)+\dfrac{1}{2}=\dfrac{1}{2}\)

c: \(=\dfrac{1}{9}\left(\dfrac{2}{9}+\dfrac{7}{9}\right)-\dfrac{8}{9}=\dfrac{1}{9}-\dfrac{8}{9}=-\dfrac{7}{9}\)

Bài 2: 

b: \(\Leftrightarrow x+\dfrac{3}{10}=\dfrac{17}{30}\)

hay x=4/15

Bình luận (0)
LT
Xem chi tiết
H24
11 tháng 12 2023 lúc 20:49

\(\dfrac{1}{x^2-x}+\dfrac{x-3}{x^2-1}\left(x\ne\pm1;x\ne0\right)\)

\(=\dfrac{1}{x\left(x-1\right)}+\dfrac{x-3}{\left(x-1\right)\left(x+1\right)}\)

\(=\dfrac{x+1}{x\left(x-1\right)\left(x+1\right)}+\dfrac{x\left(x-3\right)}{x\left(x-1\right)\left(x+1\right)}\)

\(=\dfrac{x+1+x^2-3x}{x\left(x-1\right)\left(x+1\right)}\)

\(=\dfrac{x^2-2x+1}{\left(x-1\right)\left[x\left(x+1\right)\right]}\)

\(=\dfrac{\left(x-1\right)^2}{\left(x-1\right)\left(x^2+x\right)}\)

\(=\dfrac{x-1}{x^2+x}\)

Bình luận (0)